2015
DOI: 10.1515/pjs-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Micropauses on Surgeons’ Precision After Short Laparoscopy Procedures

Abstract: Micropauses had no influence on surgical precision as evaluated after short laparoscopy procedures. The only differences were surgeon-dependent and intervention-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…As noted above, there were no statistically-significant differences in task performance among the three W/R schedules. This lack of an effect agrees with previous work showing that introducing regardless of length and duration, did not significantly influence precision task performance (Hallbeck et al, 2017;Komorowski et al, 2015;Lin et al, 2012;McLean et al, 2001). We found some evidence of differences between schedules in specific performance measures, but these effects were not consistent (see Table 3, a summary of the influences of schedules on performance measure in the three W/R schedules).…”
Section: Effects Of W/r Schedule On Task Performancesupporting
confidence: 88%
See 2 more Smart Citations
“…As noted above, there were no statistically-significant differences in task performance among the three W/R schedules. This lack of an effect agrees with previous work showing that introducing regardless of length and duration, did not significantly influence precision task performance (Hallbeck et al, 2017;Komorowski et al, 2015;Lin et al, 2012;McLean et al, 2001). We found some evidence of differences between schedules in specific performance measures, but these effects were not consistent (see Table 3, a summary of the influences of schedules on performance measure in the three W/R schedules).…”
Section: Effects Of W/r Schedule On Task Performancesupporting
confidence: 88%
“…McLean et al (2001) evaluated the effects of task duration or rest periods on typing task productivity, but found no significant difference in output. In surgical tasks, Komorowski et al (2015) and Hallbeck et al (2017) reported no significant influences of work/rest schedules on surgical precision.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Plastic surgeons often wear loupes which increase cervical loading by 40% [2], whilst other interventionalists regularly wear lead aprons which increase strain [3], [4]. A 15-pound lead apron can put approximately 300 pounds per square inch of initial pressure on the intervertebral disc [5], [6], [7], [8]. Specific procedures also appear to carry greater risk of musculoskeletal injury.…”
Section: Condition or Domain Being Studiedmentioning
confidence: 99%
“…Specific procedures also appear to carry greater risk of musculoskeletal injury. Minimally invasive surgery in particular has been reported as carrying greater risk of musculoskeletal injury [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19].…”
Section: Condition or Domain Being Studiedmentioning
confidence: 99%